identifikasi Identification of Skin Color Images in Humans Using Principal Component Analysis Method - Aurelia Fermina Kambri; Mardiani Bana; Yampi R. Kaesmetan (LP2M Universitas Widyatama, 2023)
Skin detection is an important process for classifying human skin color. Some phone cameras produce images in RGB (Red, Green, Blue) format. Various cases of skin detection often perform a transformation from the RGB color space to another color space, such as YCbCr or HSV, to improve detection accuracy. In this journal, we conduct research on skin detection using Teachable Machine, a platform that utilizes machine learning to teach computers to recognize visual patterns. The term